Analysis and Evaluation of Selected Internet Groceries - Chmielarz, Witold (Analiza i ocena wybranych internetowych sklepów spożywczych, 2010)
The aim of this article is to characterize and evaluate Internet groceries websites with regard to their quality measured by their usefulness for a potential client. In the beginning of this paper the author presented characteristics of the sector and basic methodological assumptions of the research. Next, the author conducted studies evaluating websites by means of a simple scoring method and a scoring method with preferences. The findings were analyzed and the results were compared.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 61-72
Keywords: e-business; food sector websites; quality evaluation; evaluation methods; evaluation of Internet shops